2017
DOI: 10.3847/2041-8213/aa6d09
|View full text |Cite
|
Sign up to set email alerts
|

An Earth-mass Planet in a 1 au Orbit around an Ultracool Dwarf

Abstract: We combine Spitzer and ground-based KMTNet microlensing observations to identify and precisely measure an Earth-mass (1.43 −0.46 kpc, it is the third consecutive case among the Spitzer "Galactic distribution" planets toward the Galactic bulge that lies in the Galactic disk as opposed to the bulge itself, hinting at a skewed distribution of planets. Together with previous microlensing discoveries, the seven Earth-size planets orbiting the ultracool dwarf TRAPPIST-1, and the detection of disks around young brown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 48 publications
3
124
1
Order By: Relevance
“…Second, it can probe seamlessly to the lowest-mass hosts of brown dwarfs, even into the brown-dwarf regime itself. This is a regime that is progressively less capable of forming brown dwarfs from disk material, although it may be proficient at forming Earth-mass planets (Shvartzvald et al 2017b). Third, since microlensing is most directly sensitive to the companion/host mass ratio q, it can precisely measure the distribution of this parameter, even for samples for which the individual masses are poorly known.…”
Section: Planets At the Desert's Edgementioning
confidence: 99%
See 1 more Smart Citation
“…Second, it can probe seamlessly to the lowest-mass hosts of brown dwarfs, even into the brown-dwarf regime itself. This is a regime that is progressively less capable of forming brown dwarfs from disk material, although it may be proficient at forming Earth-mass planets (Shvartzvald et al 2017b). Third, since microlensing is most directly sensitive to the companion/host mass ratio q, it can precisely measure the distribution of this parameter, even for samples for which the individual masses are poorly known.…”
Section: Planets At the Desert's Edgementioning
confidence: 99%
“…, we employ the method of Shvartzvald et al (2017b). In brief, this approach applies the VIL colorcolor relations of Bessell & Brett (1988) to a VIL crossmatched catalog of giant stars to derive an offset (including both instrumental zero point and extinction) between the intrinsic and observed (I − L) color.…”
Section: Cmd and Spitzer-ground Color-color Relationmentioning
confidence: 99%
“…However, we can securely determine the modeling parameters in this case despite the trend in the Spitzer data. Indeed, several publications used Spitzer data (which also had similar photometric systematics) to conclude that the systematics in Spitzer data are not likely to be an issue for determining modeling parameters (e.g., Poleski et al 2016;Shvartzvald et al 2017;Zhu et al 2017). …”
Section: Space-based Observationsmentioning
confidence: 99%
“…However, there exist only a few cases that have demonstrated that microlens parallaxes can be retrieved for binary lensing events with fragmentary space-based light curves without caustic-crossing features (Han et al 2017;Shvartzvald et al 2017). Indeed, Han et al (2017) used fragmentary space-based observations obtained from Spitzer to show that the microlens parallax was measured and to confirm the measurement based on the annual microlens parallax effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Spitzer microlensing program has been successful in terms of measuring masses of individual planetary systems Street et al 2016; Ryu et al 2017;Shvartzvald et al 2017) and constraining the Galactic distribution of planets (Calchi Novati et al 2015a;Yee et al 2015a;Zhu et al 2017b), there is a generic uncertainty in measuring p E with a single satellite, especially in cases of single-lens events. The microlensing parallax vector p E is directly related to the displacement between the two lenssource relative trajectories…”
Section: Introductionmentioning
confidence: 99%